Effectiveness of 5E Cycle Learning Model Assisted by Wordwall Media in Improving Critical Thinking Ability - Aldi, Muhammad; Khairanis, Retisfa; Lestari, Ana Dwi; Trinova, Zulvia (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This research aims to test the effectiveness of the 5E Learning Cycle learning model assisted by Wordwall media on critical thinking skills and student learning outcomes on ecosystem material in grade V elementary school. The research method used was a pseudo-experiment with a pretest-posttest control group design. Normality and homogeneity tests showed that the data were normally distributed and homogeneous. The results of hypothesis testing using Paired Sample T-Test showed a significant difference between experimental and control classes on critical thinking skills (sig. = 0.000) and learning outcomes (sig. = 0.036). Furthermore, MANOVA analysis showed that the learning model simultaneously affected critical thinking skills and learning outcomes (sig. = 0.000). The Between-Subjects Effects test also confirmed the results that the treatment variable (the use of the 5E model with Wordwall) had a significant effect on variable Y1 (critical thinking) with Fhitung = 38.868 and on variable Y2 (learning outcomes) with Fhitung = 4.645. Thus, it can be concluded that the 5E Learning Cycle learning model assisted by Wordwall media effectively improves students’ critical thinking skills and learning outcomes on ecosystem material in class V elementary school Neger 23 Ampalu Kota Padang.